Immune dysregulation in patients with PTEN hamartoma tumor syndrome: Analysis of FOXP3 regulatory T cells - Chen, H; Handel, N; Ngeow, J; Muller, J; Huhn, M; Yang, H; Heindl, M; Berbers, R; Hegazy, A; Kionke, J; Yehia, L; Sack, U; et al. (Elsevier, 2016)
Background: Patients with heterozygous germline mutations in PTEN (phosphatase and tensin homologue deleted on chromosome 10) develop autoimmunity and lymphoid hyperplasia. Objectives: Since regulation of the phosphoinositol-3-kinase (PI3K) pathway is critical for maintaining regulatory T cell (Treg) functions we investigate Tregs in patients with heterozygous germline PTEN mutations (PTEN harmatoma tumour syndrome, PHTS). Methods: PHTS patients were assessed for immunological conditions, lymphocyte subsets, FOXP3+ Treg levels and phenotype. To determine the functional importance of phosphatases that control the PI3K pathway we assessed Treg induction in vitro, mitochondrial depolarization, and recruitment of PTEN to the immunological synapse. Results: Autoimmunity and peripheral lymphoid hyperplasia was found in 43% of 79 PHTS patients. Immune dysregulation in PHTS patients included lymphopenia, CD4+ T cell reduction and changes in T and B cell subsets. Although total CD4+FOXP3+ Treg numbers are reduced, frequencies are maintained in blood and intestine. Despite pathogenic PTEN mutations, the FOXP3+ T cells are phenotypically normal. We show that the phosphatase PHLPP downstream of PTEN is highly expressed in normal human Tregs and provides complementary phosphatase activity. PHLPP is indispensable for the differentiation of induced Tregs in vitro and Treg mitochondrial fitness. PTEN and PHLPP form a phosphatase network that is polarized at the immunological synapse. Conclusion: Heterozygous loss of function of PTEN in humans has an significant impact on T and B cell immunity. Assembly of the PTEN-PHLPP phosphatase network allows coordinated phosphatase activities at the site of T cell receptor activation, which is important for limiting PI3K hyperactivation in Tregs despite PTEN haploinsufficiency.